Lembaga Pendidikan Islam Ideologis dalam arus pembaruan Pendidikan Islam di Indonesia - Nisfatul Laela; Salsa Romadhon; Sutrimo Purnomo (Jurnal Pendidikan Agama Islam, 2026)
Educational institutions play an important role in shaping individuals’ knowledge, skills, and character. Etymologically, an institution can be understood as a structure or system that serves specific functions and purposes, both in physical and non-physical forms. In the educational context, institutions are not only limited to formal organizations such as schools, but also include various social environments that contribute to the learning process. Education is essentially a lifelong process that occurs through continuous interaction between individuals and their surroundings. In practice, the implementation of education cannot be separated from ideology, which forms the foundation for determining educational goals, directions, and values. Ideology influences how society perceives education and is often transmitted through social institutions such as families and schools. In the context of Islamic education, the concept of education emphasizes not only the transfer of knowledge but also the development of moral values and character. This perspective is reflected in the concepts of tarbiyah, ta’lim, and ta’dib, which highlight the holistic development of individuals in intellectual, moral, and spiritual dimensions. Therefore, educational institutions have a strategic role in forming individuals who are not only intellectually capable but also possess strong character and ethical values.